An Expanded Analysis of Pharmacogenetics Determinants of Efavirenz Response that Includes 3′-UTR Single Nucleotide Polymorphisms among Black South African HIV/AIDS Patients - Swart, Marelize; Evans, Jonathan; Skelton, Michelle; Castel, Sandra; Wiesner, Lubbe; Smith, Peter J.; Dandara, Collet (Frontiers in Genetics, 2016)
Introduction: Efavirenz (EFV) is a non-nucleoside reverse transcriptase inhibitor prescribed as part of first-line highly active antiretroviral therapy (HAART) in South Africa. Despite administration of fixed doses of EFV, inter-individual variability in plasma concentrations has been reported. Poor treatment outcomes such as development of adverse drug reactions or treatment failure have been linked to EFV plasma concentrations outside the therapeutic range (1–4 μg/mL) in some studies. The drug metabolizing enzyme (DME), CYP2B6, is primarily responsible for EFV metabolism with minor contributions by CYP1A2, CYP2A6, CYP3A4, CYP3A5, and UGT2B7. DME coding genes are also regulated by microRNAs through targeting the 3′-untranslated region. Expanded analysis of 30 single nucleotide polymorphisms (SNPs), including those in the 3′-UTR, was performed to identify pharmacogenetics determinants of EFV plasma concentrations in addition to CYP2B6 c.516G>T and c.983T>C SNPs. Methods: SNPs in CYP1A2, CYP2B6, UGT2B7, and NR1I2 (PXR) were selected for genotyping among 222 Bantu-speaking South African HIV-infected patients receiving EFV-containing HAART. This study is a continuation of earlier pharmacogenetics studies emphasizing the role of genetic variation in the 3′-UTR of genes which products are either pharmacokinetic or pharmacodynamic targets of EFV. Results: Despite evaluating thirty SNPs, CYP2B6 c.516G>T and c.983T>C SNPs remain the most prominent predictors of EFV plasma concentration. Conclusion: We have shown that CYP2B6 c.516G>T and c.983T>C SNPs are the most important predictors of EFV plasma concentration after taking into account all other SNPs, including genetic variation in the 3′-UTR, and variables affecting EFV metabolism.